Application Design of A Multiple Power Source Monitoring System Based On The Internet Of Things (IOT) - Multi, Abdul; Mujiburohman; Wardana, Kun (Green Publisher, 2024)
At the present time, technology is developing rapidly in various scientific fields. People continue to develop and research the latest technologies to make human life easier. One of them is in the field of IoT (Internet of Things) technology. The use of electrical devices in each power source has different electrical power consumption. And this often happens, so when using electrical equipment, each power source is a tool for monitoring the use of electrical power, so that the use of electrical power in multiple power sources is in accordance with the required power. Therefore, a tool is designed that can facilitate the performance of activities to monitor the use of electric power, the results of which can be displayed through LCD 16X2 and can be informed through the Internet. The purpose of this research is to design an IoT-based electric power monitoring system to facilitate the monitoring of electric power consumption in multiple IoT-based power sources. The method used in data collection is quantitative method. With the collection of several components needed, which are designed in this study such as voltage sensors, Ethernet shields, hub switches and Arduino Uno microcontrollers. This research will monitor IoT-based power, and can be monitored via the Internet in the form of a graphical display on a desktop application or in the form of a monitoring web page. The results showed that the average error value in testing the voltage sensor was 0.02%, the sensor for current readings had an error value of 0.19%, and the value of power was 0.18%. So it can be concluded that by having a fairly small difference and error, this tool is said to be quite good and then by testing the monitoring application system on the web page that is made capable of sending, storing and displaying data on the monitoring web page in real time every minute even with different power sources, in tests conducted with two different power sources and can be measured properly, so that testing the web monitoring application can be said to be good because it can monitor electrical power of multiple power sources.